Effect of Direct Antiviral Therapy Against HCV on CD4+ T Cell Count in Patients with HIV-HCV Coinfection - Pinchera B; Zappulo E; Buonomo AR; Cotugno MR; Di Filippo G; Borrelli F; Mercinelli S; Villari R; Gentile I (HIV/AIDS: Research and Palliative Care, 2023)
Biagio Pinchera, Emanuela Zappulo, Antonio Riccardo Buonomo, Maria Rosaria Cotugno, Giovanni Di Filippo, Francesco Borrelli, Simona Mercinelli, Riccardo Villari, Ivan Gentile Department of Clinical Medicine and Surgery, Section of Infectious Diseases, University of Naples “Federico II”, Naples, ItalyCorrespondence: Biagio Pinchera, Email biapin89@virgilio.itBackground: HCV-related liver disease is an important cause of morbidity and mortality in patients with HIV infection. It is well known that the response rates to HCV therapy are similar between HCV-monoinfected patients and HIV-HV coinfected ones. The aim of this study was to evaluate the impact of HCV eradication on CD4 + T cell count in a population of HIV-HCV coinfected patients.Materials and Methods: We enrolled patients with HIV-HCV coinfection attending the Infectious Diseases Unit of the A.O.U. Federico II of Naples, from January 2016 to February 2019, treated with ART (AntiRetroviral Therapy) and DAAs (Direct Antiviral Agents). For each patient, we evaluated HIV and HCV viral load and CD4+ T cell count before starting therapy with DAAs, by SVR12 time and by SVR48 time. Fibrosis was evaluated by the mean of Fibroscan®.Results: Fifty-two patients were enrolled, 40 males. Fibrosis score was F0-F3 in 15 patients and cirrhosis in the remaining 11 (all in Child-Pugh class A). All had been receiving ART, and all were treated with DAAs. Only patient who had not achieved HIV viral suppression for non-compliance also experienced a relapse of HCV infection after the end of DAAs. In all patients, we observed that the CD4+ T cell count at baseline did not show significant variations compared to SVR12 and SVR48 time. We also assessed CD4 count in relation to HIV categories and stage of liver disease, see Table 1. Also, based on the assessments of the subclasses considered, there were no significant changes in the CD4 + T cell count.Conclusion: Our study shows that HCV viral eradication obtained with DAAs in patients with HIV-HCV coinfection is not associated with significant changes in the CD4 + T cell count, regardless of CDC category and stage of liver disease.Keywords: HCV, HIV, fibrosis, cirrhosis, DAAs, CD4+ T cell, coinfection